Physiological parameters, yield and seed quality of wheat as influenced by irrigation and split application of nitrogen - Hossain, Md Belal; Hasan, Md Mahmodol (Fundamental and Applied Agriculture, 2018)
The experiment was conducted at the Agronomy Field Laboratory, University of Rajshahi to study the effect of moisture stress and nitrogen split application on the physiological parameters, yield and seed quality of wheat. Four moisture treatments viz. control, one irrigation at crown root initiation (CRI) stage, two irrigations, at CRI and stem elongation stages and three irrigations, at CRI, stem elongation and flowering stages; and four nitrogen treatments viz. control, basal application, 1/2 basal + 1/2 top dressed at 1st irrigation and 1/3 basal + 1/3 top dressed at 1st irrigation + 1/3 top dressed at 2nd irrigation were used. Results showed that total dry matter (TDM), crop growth rate (CGR) and leaf area index (LAI) increased with the increase of number of irrigation. Three irrigations produced the highest TDM, CGR and LAI. The highest net assimilation rate (NAR) was found in control at all sampling dates except 65 to 80 DAS. Growth parameters like TDM, CGR and LAI increased with the increase of splits of nitrogen application. Three splits of nitrogen showed the highest TDM, CGR, and LAI. Grain and straw yields were varied significantly due to irrigation levels. Grain and straw yields were increased with the increase of irrigation frequencies. The highest grain and straw yields were found in three irrigations. Grain and straw yields were found to be significant in respect of nitrogen splits. Significantly the highest values were observed in three splits of nitrogen. Irrigation had significant effect on all most all seed quality parameters. The highest germination, vigour index, nitrogen content in grain and protein content in grain were obtained in three irrigations. With some exceptions, the highest germination, vigour index, nitrogen content in grain and protein content in grain were found in three splits of nitrogen. Interaction effects of irrigation and nitrogen splits was significant for almost all the parameters. with some exception, the highest value was obtained from three irrigations with three splits of nitrogen (I3×N3) treatment combination for almost all the cases. From the results it may be concluded that application of nitrogen in three equal splits at basal, crown root initiation and stem elongation stages and three times irrigation at crown initiation, stem elongation and flowering stages is better for maximizing yield and seed quality of wheat.